Lessons Learned in 11 Years of Experience With Open Abdomen Treatment With Negative-Pressure Therapy for Various Abdominal Emergencies - Gasser, Elisabeth; Rezaie, Daniel; Gius, Johanna; Lorenz, Andreas; Gehwolf, Philipp; Perathoner, Alexander; Öfner, Dietmar; Kafka-Ritsch, Reinhold (Frontiers in Surgery, 2021)
Introduction: Open abdomen treatment (OA) with negative-pressure therapy (NPT) was initiated for perforated diverticulitis and subsequently extended to other abdominal emergencies. The aim of this retrospective study is to analyse indications, procedures, duration of NPT and outcome of all our patients. Methods: All consecutive patients treated with intra-abdominal NPT from 1.1.2008 to 31.12.2018 were retrospectively analysed. Results: A total of 438 patients (44% female) with a median(range) age of 66(12-94), BMI of 25(14-48) and an ASA score I/II/III/IV of 36(13%)/239(55%)/95(22%)/3(1%) were treated with NPT. The indication for surgery was primary bowel perforation in 163(37%), mesenteric ischemia in 53(12%), anastomotic leakage in 53(12%), ileus in 53(12%), postoperative bowel perforation/leakage in 32(7%), abdominal compartment in 15(3%), pancreatic fistula in 13(3%), gastric perforation in 13(3%), secondary peritonitis in 11(3%), burst abdomen in 9(2%), biliary leakage in 8(2%) and other in 15(3%) patients. A damage control operation without reconstruction in the initial procedure was performed in 164(37%) patients. Duration of hospital and intensive care stay was median(range) 28(0-278) and 4(0-214) days. Median(range) duration of operation was 109(22-433) minutes and of NPT therapy 3(0-33) days. A trend to shorter duration of NPT was observed over time and in the colonic perforation group. Mean operating time was shorter when only blind ends were left in situ, namely 110 vs 133 minutes (p=0.006). The mortality rate was 14% at 30 days, 21% at 90 days and 31% at one year. An entero-atmospheric fistula was observed in 5(1%) cases, most recently in 2014. Direct fascia closure was possible in 417(95%) patients at the end of NPT, but least often (67%, p=0.00) in patients with burst abdomen. During follow-up, hernia repair was observed in 52(24%) of the surviving patients. Conclusion: Open abdomen treatment with NPT is a promising concept for various abdominal emergencies, especially when treated outside normal working hours. A low rate of entero-atmospheric fistula formation and a high rate of direct fascia closure were achieved with dynamic approximation of the fascia edges. The authors recommend an early in and early out strategy as prolongation of NPT by more than one week does not improve abdominal sepsis.